Use and value of Quechua in Arequipa - Ccalla Mamani, Julian (2022)
This research studies the use and value of Quechua in Arequipa. Methodologically, the research is of a descriptive ethnographic qualitative approach. The discourses correspond to three collaborators from different occupations. One of them is a migrant from Puno, who speaks Spanish and Quechua (bilingual) and is in Arequipa; while the other two are Spanish speakers (monolingual), natives of the city. The study concludes that the bilingual collaborator shows a competence of use and identifies with Quechua during her interpersonal and family communication. In contrast, the monolingual speakers lack mastery of the native language because they do not use it actively, although they emphasize the importance that should be given to Quechua in Arequipa.